Multifaceted Role of Neuropilins in the Immune System: Potential Targets for Immunotherapy - Roy, Sohini; Bag, Arup K.; Singh, Rakesh K.; Talmadge, James E.; Batra, Surinder K.; Datta, Kaustubh (Frontiers in Immunology, 2017)
Neuropilins (NRPs) are non-tyrosine kinase cell surface glycoproteins expressed in all vertebrates and widely conserved across species. The two isoforms, NRP1 and NRP2 mainly act as co-receptors for class III Semaphorins and for members of the Vascular Endothelial Growth Factor (VEGF) family of molecules and are widely known for their role in a wide array of physiological processes like cardiovascular, neuronal development and patterning, angiogenesis, lymphangiogenesis as well as various clinical disorders. Intriguingly, additional roles for NRPs occur with myeloid and lymphoid cells, in normal physiological as well as different pathological conditions, including cancer, immunological disorders, and bone diseases. However, little is known concerning the molecular pathways that govern these functions. Additionally, NRP1 expression has been characterized in different immune cellular phenotypes including macrophages, dendritic cells (DCs), and T cell subsets, especially regulatory T cell (Treg) populations. In contrast, the functions of NRP2 in immune cells is less well known. In this Review, we briefly summarize the genomic organization, structure, and binding partners of the NRPs, and extensively discuss the recent advances in their role and function in different immune cell subsets and their clinical implications.